Development of Protein Rich Flour (PRF) from Hyacinth Bean (Lablab purpureus (L) Sweet) and Lima bean (Phaseolus lunatus) - Ahmad Nafi; Tri Susanto; Achmad Subagio (Jurnal Teknologi dan Industri Pangan, 2006)
With respect to the high content of carbohydrate and protein, Protein Rich Flour (PRF) were developped from non-oilseed legumes i.e. hyacinth bean (Lablab purpureus (L) Sweet) and lima bean (Phaseolus lunatus) PRF. PRFs were prepared using water and NaOH solution (0.01N) as the extraction solvent. After precipitation in their isoelectric point (pHs) the PRFs produced were characterized to determine the potential practical applications. The results showed that PRF from hyacinth bean extracted by water was the best product with yield of 31.19%, protein content of 58.41±4.45%, solubility of 82-100% and oil holding capacity being 93.92±9.19. Moreover pepsin-digestibility of the hyacinth bean PRF was higher (8.29±0.34%) than soybean protein isolate (7.10±0.37%) or casein (7.04±0.14%). Based on their characteristics, PRF is regarded as potential to be developed as novel food ingredient. Key words: Non-oilseed Legumes, PRF, Characterization